Consumers' credit card bankruptcy: Cause and effect - Zaminor Zamzamir@Zamzamin; Azila Jaini; Siti Zamanira Mat Zaib; Che Rusuli M. S. (Medwell Journals, 2016)
A number of studies have pointed to various mistakes that credit card users might make in their consumption-saving and financial decisions. Recently, young users like to hold a number of credit card which is automatically they have a power of spending money. Some people claimed that by having a number of credit cards, it will reflect someone socio-economy status. Without realizing the impact of the excess usage of credit card young users were declaring bankrupt due to credit card debts. This study discussed the bankruptcy issues among young users of a credit card in Malaysia. The results disclose that the compulsive spending is more influenced towards the factors that lead to bankruptcy in the early age of credit card user.